2004
DOI: 10.1525/eth.2004.32.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Between East and West: Geographic Metaphors of Identity in Poland

Abstract: As Poland enters the European Union, questions of national identity relative to wider group loyalties become particularly salient. This study considers how individual life stories contribute to the discourse on what constitutes the Polish nation, and contemplates the implications of respondents' views for the achievement of European integration. I focus on Polish youths' use of metaphors of "betweenness," in which Poland fills the conceptual space between East and West, and "nested identities," based on simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A similar rhetoric was voiced by Jacek, who again depicted transition as something observed and experienced through the enhanced local built environment, commenting on how colourful his surroundings became, colour being an important trope in discourses of post‐socialist ‘westernisation’ (see Burrell 2011; Galbraith 2004, 63):…”
Section: Narrating Opportunity and Changementioning
confidence: 92%
See 1 more Smart Citation
“…A similar rhetoric was voiced by Jacek, who again depicted transition as something observed and experienced through the enhanced local built environment, commenting on how colourful his surroundings became, colour being an important trope in discourses of post‐socialist ‘westernisation’ (see Burrell 2011; Galbraith 2004, 63):…”
Section: Narrating Opportunity and Changementioning
confidence: 92%
“…The positivity of these accounts is, on first analysis, quite striking. In her research with young people in Poland in 1992 and 1993, Galbraith (2004, 63–4) found that disillusionment with new goods and businesses associated with the west was already setting in during the early years of the decade. Although one or two respondents spoke of the ‘idiotic’, disappointing television programmes they could now watch – Patrycja (born in 1980, came to Britain in 2004), for example, talked scathingly about western dog shows – this scepticism towards the new consumer environment was not a strong theme in the interviews.…”
Section: Narrating Opportunity and Changementioning
confidence: 99%
“…Then, there is the relation to eastern and third world ‘others’, including those living in the pre-war Polish territories in the near East, who are often viewed in civilisational terms. Poland’s position within this discursive framing is not simply an ‘inbetweeness’ (in between East and West), as some scholars have argued ( Galbraith, 2004 ; Janion, 2011 ), it is something much more complex. These three axes operate in parallel, and the outcomes of competing discourses, spheres of influence, racial and social hierarchies, distinctions between ‘insider’ and ‘outsider’, the ‘self’ and the ‘other’ manifest themselves in complex and contradictory ways.…”
Section: Poland Through a Postcolonial Lensmentioning
confidence: 99%
“…Colour and visual life, however – and in particular the denotation of a ‘grey’ communist bloc – are almost ubiquitous in accounts of socialism across the Soviet Union and eastern Europe. Galbraith (2004, 63), moreover, using narratives collected with youths in the 1990s, notes how post‐socialist ‘transition’ in Poland has been perceived as a ‘process of colorization’, with the ‘grey’ gradually giving way to the more vibrant and varied colours of adverts and new shop fronts. Colour, therefore, can be understood as a potent vehicle for expressing perceptions of what is eastern and what is western, so powerful in fact, that, as with the earlier discussion of memory and socialism, it is impossible to know how much this wider rhetoric has influenced the individual testimonies themselves.…”
Section: Consuming Colouring and Domesticating The Westmentioning
confidence: 99%